GATA1-mutant clones are frequent and often unsuspected in babies with Down syndrome: identification of a population at risk of leukemia. - Roberts, I; Alford, K; Hall, G; Juban, G; Richmond, H; Norton, A; Vallance, G; Perkins, K; Marchi, E; McGowan, S; Roy, A; Cowan, G; et al. (American Society of Hematology, 2013)
Transient abnormal myelopoiesis (TAM), a preleukemic disorder unique to neonates with Down syndrome (DS), may transform to childhood acute myeloid leukemia (ML-DS). Acquired GATA1 mutations are present in both TAM and ML-DS. Current definitions of TAM specify neither the percentage of blasts nor the role of GATA1 mutation analysis. To define TAM, we prospectively analyzed clinical findings, blood counts and smears, and GATA1 mutation status in 200 DS neonates. All DS neonates had multiple blood count and smear abnormalities. Surprisingly, 195 of 200 (97.5%) had circulating blasts. GATA1 mutations were detected by Sanger sequencing/denaturing high performance liquid chromatography (Ss/DHPLC) in 17 of 200 (8.5%), all with blasts >10%. Furthermore low-abundance GATA1 mutant clones were detected by targeted next-generation resequencing (NGS) in 18 of 88 (20.4%; sensitivity ∼0.3%) DS neonates without Ss/DHPLC-detectable GATA1 mutations. No clinical or hematologic features distinguished these 18 neonates. We suggest the term "silent TAM" for neonates with DS with GATA1 mutations detectable only by NGS. To identify all babies at risk of ML-DS, we suggest GATA1 mutation and blood count and smear analyses should be performed in DS neonates. Ss/DPHLC can be used for initial screening, but where GATA1 mutations are undetectable by Ss/DHPLC, NGS-based methods can identify neonates with small GATA1 mutant clones.